Essential criteria for reporting of aromatherapy-focused research in humans: An international Delphi consensus study protocol - Marian Elaine Reven; Esther Joy Bowles; Kelly Ablard; Marilyn Peppers-Citizen; Amanda May-Fitzgerald; Denise Joswiak; Bethany Unger (PLoS ONE, 2025)
Background Reporting quality of aromatherapy-focused research in humans is inconsistent and often incomplete yet there are no (North American or American) nationally or internationally agreed upon core criteria for aromatherapy-focused research. The Aromatic Research Quality Appraisal Task Force developed the Transparent Reporting for Essential oil and Aroma Therapeutic Studies (TREATS) checklist as initial steps toward developing a reporting guideline. The purpose of this Delphi study is to engage with an international community of aromatherapy researchers to reach consensus on which items should be included in reports of aromatherapy-focused studies in humans. The result of the consensus process will be to publish an aromatherapy research reporting guideline that can be used as an extension to existing research reporting guidelines for various studies such as randomized controlled trials, observational studies, and case reports. Methods A modified Delphi consensus study will be used. The consensus study, approved by the West Virginia University Institutional Review Board, will consist of up to four rounds of an online survey. To improve understanding and buy-in, experts attending a large international aromatherapy-focused conference will take part in a four-hour in-person/virtual hybrid introductory meeting where they can learn the study process and ask questions. The 48-item survey is divided into categories covering study products, processes, aromatherapy intervention, safety, sustainability, and olfactory ability and aroma preference. Participants will be asked to rate each checklist item for relevance on a 5-point Likert scale ranging from “of little importance” to “extremely important”. During the Delphi study, participants can provide comments and, in the first and second rounds, may suggest additional items or modifications to existing items. An item will be automatically included in the final guidelines if it is rated as "very important" or "extremely important" by at least ≥80% of the participants in Rounds 1–3, and automatically excluded if > 50% of participants rate the item as “not important” or “of little importance”. Aggregated ratings will be statistically analyzed for response rates, level of agreement, medians, and interquartile ranges. Discussion This protocol supports conducting a Delphi consensus that will add to the current knowledge of items considered necessary for complete and consistent reporting of aromatherapy-focused research in humans. This is of international significance as world-wide use and research of aromatherapy and essential oils in humans has continued to increase, currently without consistent and clear reporting. The Delphi method is appropriate for developing consensus between diverse experts, researchers, and practitioners as it offers anonymity and minimizes bias. Findings will contribute to creating an extension to primary reporting guidelines.